CULTURAL CODES SYSTEM OF “AKHBAR AL-SHU’ARA” ABU BAKR AL-SULI (Journal of Oriental Studies, 2024)
This paper investigates the system of culture/cultural codes in "Akhbar al-Shu'ara" of the Abbasid author Abu Bakr al-Suli (10th century). Three - dimensional - social, religious, and temporal-spatial, system is distinguished by its hierarchy and binary oppositions. At the same time, religious and social codes show similar signs of a practical and theoretical nature. Their comparison makes possible to trace development features of the Arab-Muslim society in the 8th-9th centuries: from family to tribe, then to social strata and the state. The generalized “people” and the author’s “I” concepts play an important role in the behavioral patterns presented in the cultural codes. The temporal-spatial aspect, inferior in quantitative indicators to the previous two, nevertheless has an important function because it creates a connection and integrates different periods of the historical time. All these make al-Suli’s work comprehensive one from the point of view of modern perception.
Keywords: “Akhbar al-Shu'ara”; Abu Bakr al-Suli; Cultural Codes; Binary Oppositions; Abbasid Caliphate; Arab-Muslim Community; Medieval Arab Culture